Osteoinductive potential of non-polar piper sarmentosum extract in a stem cell-based bone regeneration model - Intan Zarina Zainol Abidin; Anis Nabilah Johari; Muhammad Dain Yazid; Asmah Awal; Zaidah Zainal Ariffin; Shahrul Hisham Zainal Ariffin (Penerbit Universiti Kebangsaan Malaysia, 2026)
Piper sarmentosum (PS), a medicinal plant with pharmacological properties, has yet to be investigated for its potential in stem cell-based osteogenesis using non-polar extracts. This study investigated the osteoinductive potential of a hexane based extract of PS on human peripheral blood stem cells (PBSCs). PBSCs were cultured for 14 days and characterized using SLAMF1 and CD34 stem cell markers. PBSCs were treated with several concentrations of the PS hexane extract to induce osteoblast differentiation. Osteoblast differentiation was assessed through alkaline phosphatase (ALP) activity, mineralization assays, and osteoblast-specific gene expression profiling (ALP, RUNX2, OPN, OCN). Gas chromatography mass spectrometry (GC-MS) analysis identified 13 non-polar bioactive compounds in the extract, with β-asarone and phytol as predominant constituents. The 1 μg/mL concentration of the extract demonstrated optimal osteogenic potential, as evidenced by ALP activity comparable to positive controls, increased mineral deposition, and upregulation of osteogenic genes. These findings suggest that non-polar compounds in PS extract, especially β-asarone and phytol, possess osteoinductive properties, offering a potential natural approach for bone regeneration applications via stem cell-mediated pathways.